Values and education within the framework of Islamisation of knowledge - Berghout, Abdul Aziz (IIUM Press, 2011)
This paper examines the relationship between values and education within the framework of [slamisation of KnO\vledge. It shows the importance of values and ethics in the process of knowledge creation, application and dissemination reflecting an integrated model of education. Within the framework of Islamisation of knowledge education appears more holistic and all encompassing with primary emphasis on the person as a whole including; his/her mind, soul, heart, body, character, skills, social relations and over all bringing up.